Charles Williams : the third Inkling - Lindop, Grevel, 1948- (Oxford University Press, 2015)
A lively and readable literary biography of a remarkable personality who was a central member of the Inklings, this book rediscovers the dramatic and contradictory life of a brilliant writer and publisher from a poor London background who became a ground-breaking theologian, fantasy novelist and poet.